DOES EXCESSIVE ABSENCE FROM CLASS LEAD TO LOWER LEVELS OF ACADEMIC ACHIEVEMENT? - Mohannad Eid AbuRuz (European Scientific Journal, ESJ, 2015)
There is a general agreement among researchers that being chronically absent places students at risk for negative academic consequences. However, some studies have failed to find a significant correlation between attendance and academic performance. Studies examining this relationship are lacking at the field of Nursing. The purpose of this study was to check the effect of absenteeism rate on the academic achievement of graduate and undergraduate nursing students at a private university in Amman, Jordan. A cross-sectional correlational design was used with a sample of 130 BSN and 40 Master students. Results showed that students who have higher absenteeism rates have lower Grand Point Average (GPA) regardless to academic level. Moreover, Male students have higher absenteeism rates and lower GPAs than females. In conclusion, the present study has reported a negative correlation between absenteeism and academic achievement. Application of attendance polices might help in improving students’ attendance and their academic achievement.